Federal-state relations in Sabah, Malaysia the Berjaya administration, 1976-85 - Lim, Regina 1973- (Institute of Southeast Asian Studies, 2008)
A study of the political development of the Malaysian state of Sabah under the administration of Parti Bersatu Rakyat Jelata Sabah (Berjaya - Sabah People's United Party), which controlled the state legislature between 1976 and 1985.